Pembangunan modul pedagogi kelas berbalik berasaskan pembelajaran reflektif untuk politeknik premier / Zanariah Ahmad - Zanariah, Ahmad (2017)
This study aimed at developing a flipped classroom pedagogical module based on reflective learning at premier polytechnics in resolving students’ incapability to link skills with knowledge. The Design and Development Research methodology as introduced by Richey and Klein (2014) was used in this study involving three phases. Data from the first phase, the needs analysis, were collected through questionnaires administered on 200 students in a Mechanical Engineering Diploma program from three premier polytechnics. The data were analyzed using descriptive statistics by the Statistical Packages for the Social Sciences (SPSS) version 21. The findings of the first part in the second phase, the module design, were obtained through the Fuzzy Delphi technique involving 23 experts in Curriculum, Technical and Vocational, Mechanical Engineering, and Instructional Technology field. The analysis relied on the experts’ responses to the questionnaire based on a Fuzzy Linguistic Likert Scale. The threshold d value was calculated to determine the experts’ consensus on all questionnaire items. The data of the second part in the second phase, the module development, involved refinement of lesson plans and learning materials in video format for Vector Force topic, with validation by four experts. In the third phase, the module effectiveness was tested using quasi-experimental design. The comparison of achievements between the treatment and control group was conducted based on the pre and post-test results. The findings of the first phase indicated that students have the ability and access to technological tools and computers, and have positive perceptions toward using computer and e-learning platforms. The findings of the first part in the second phase, the module design, revealed that the experts have achieved unanimous consensus with the threshold d value ≤0.2, exceeded 75% on the suitability of items in the learning module. The findings of the second part in the second phase of module development suggested a number of improvisations, especially on the use of video and pop quiz. In the third phase, the module evaluation, the result of paired sample t-test indicated that there was a significant difference between both groups, with p = .000 (p < 0.05). Also, the eta- squared effect size test indicated that the treatment group has a higher effect size